Gerakan Pakan Mandiri (Gepari) : Teknologi Pelet Ikan Solusi Pemberdayaan Kewirausahaan Santri (Santripreneur) di Pondok Pesantren Bahrul Maghfiroh Malang - Maftuch Maftuch (Journal of Innovation and Applied Technology, 2021)
Potential higher market demand in Malang provides an opportunity for Islamic boarding schools to participate in this section. The problems experienced by all cultivators are weak formulation of fish feed, especially waste and lack of knowledge of feed formulations and current feed prices soaring and starting to burden the cultivators. Therefore, a new innovation is needed for the independent feed movement that has better nutritional content at a much more affordable price and generates tangible benefits. The problems experienced by Pondok Pesantren Bahrul Maghfiroh can be overcome through the implementation of the Independent Feed Movement (Gepari) by utilizing raw materials for livestock waste, vegetable waste. This is due to its nutritional and nutritional content that fulfill the innovative concept of multiple completion.